ETIKA PENGGUNAAN MEDIA SOSIAL SESUAI SILA KEDUA - Gita Dwi Mutia; Mainar Fitri; Rike Juliansari; Eva Siti Fadilla (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The increasingly massive use of social media requires special attention to the ethics carried out by its users. The second principle of Pancasila,